A Density Functional Theory Study on using Montmorillonite to Reduce Air Pollution - Wungu, Triati Dewi Kencana; Yusfi, Meqorry; Suprijadi, Suprijadi (Makara Journal of Technology, 2020)
In this study, density functional theory (DFT) method is used to investigate the possibility of using a smectite clay mineral called montmorillonite (MMT) in reducing heavy metals, such as Cd, through Cd adsorption. The mechanism of Cd adsorption in MMT is observed theoretically, and the tetrahedrally isomorphic substitution on the upper layer of MMT is considered to observe the role of Al and Fe in strengthening Cd adsorption. Two types of MMT are modeled in this study: Al-MMT and Fe-MMT. The Al-MMT means that Al substitutes one atom in the upper tetrahedral layer of MMT, while Fe-MMT means that Fe substitutes one atom in the upper tetrahedral layer of MMT. According to the DFT calculation, Cd is adsorbed relatively strongly to Al-MMT compared with Fe-MMT, with Cd adsorption energy of –4.55 eV and –2.43 eV for Al-MMT and Fe-MMT, respectively. The density-of-state analysis shows that Cd helps reduce the gap between the highest valence-band energy and lowest conduction-band energy of Al-MMT and Fe-MMT. Thus, Cd/Al-MMT and Cd/Fe-MMT behave in a manner similar to a semiconductor.